Single Ablative Fractional Resurfacing Laser Treatment For Forearm Actinic Keratoses: 6‐Month Follow‐Up Data From An Intrapatient Comparison Between Treated and Untreated Sites. Issue 1 (17th November 2019) - Chen, Roy; Wargo, Jeffrey J.; Williams, Amy; Cates, Elizabeth; Spandau, Dan F.; Knisely, Christina; Travers, Jeffrey B.
Abstract : Background and Objectives: Actinic keratoses (AK) are common pre‐cancerous lesions, which are associated with ultraviolet light exposure and aging. Wounding therapies such as fractionated laser resurfacing (FLR) have been previously demonstrated to effectively treat facial AK. However, the effectiveness of FLR on other sites commonly afflicted with AK has not been studied in detail. Previously, our group has reported that treatment of aged skin with wounding therapies including dermabrasion and ablative fractionated resurfacing results in the removal of senescent fibroblasts and normalizing the pro‐carcinogenic acute ultraviolet B radiation responses associated with aged skin. The current studies were designed to test the effectiveness of FLR of the forearm skin of subjects aged 60 and older to remove AKs. Study Design/Materials and Methods: Between February 2018 and March 2019, 30 subjects were enrolled in a study, in which they underwent a single FLR treatment of one extremity including the dorsal forearm, wrist, and dorsal hand. The number of AKs was recorded on both extremities at baseline, 3 and 6 months in a blinded fashion. Side effects of the FLR were documented. Results: A single FLR treatment resulted in a 62% reduction in the absolute number of AK in the treated arm at 6 months post‐treatment. The laser treatment was well‐tolerated without major complications. Conclusions: These studies demonstrate that FLR using settings, which have demonstrated to remove senescent fibroblasts and normalize the pro‐carcinogenic UVB‐response of aged skin is a potentially effective and safe field therapy treatment that should be studied for long‐term efficacy for use in treating upper extremity AKs. Lasers Surg. Med. © 2019 Wiley Periodicals, Inc.